Math, asked by Ataraxia, 3 months ago

Find the following integral :-
\displaystyle \sf \int e^{2x}sin3x \ dx

Answers

Answered by assingh
30

Topic :-

Indefinite Integration

To Solve :-

\sf{I=\displaystyle \int e^{2x}\sin 3x\:dx}

Concept Used :-

Integration by Parts

\sf{\displaystyle \int uv \:dx = u\int v\:dx - \int \left(\dfrac{du}{dx}\int v\:dx \right)dx}

where u and v are differentiable functions.

u and v are generally chosen as per the order of the letters in ILATE, where

I represents Inverse Trigonometric Function

L represents Logarithmic Function

A represents Algebraic Function

T represents Trigonometric Function and

E represents Exponential Function

Solution :-

\sf{I=\displaystyle \int e^{2x}\sin 3x\:dx}

\sf{Taking\:u=\sin3x \:and\:v=e^{2x}\:as\:per\:ILATE.}

Applying Integration by parts,

\sf{I=\displaystyle\sin3x\int e^{2x}\:dx - \int \left(\dfrac{d(\sin 3x)}{dx}\int e^{2x}\:dx \right)dx}

\sf{I=\displaystyle\sin3x\cdot\dfrac{e^{2x}}{2} - \int \left(\dfrac{d(\sin 3x)}{dx}\cdot\dfrac{e^{2x}}{2}\right)dx}

\sf{\left(\because\displaystyle \int e^{ax}\:dx=\dfrac{e^{ax}}{a}+C \right)}

\sf{\displaystyle I=\sin3x\cdot\dfrac{e^{2x}}{2} - \int \left(\cos3x\cdot\dfrac{d(3x)}{dx}\cdot\dfrac{e^{2x}}{2}\right)dx}

\sf{\left(\because \dfrac{d(\sin t)}{dx}=\cos t\cdot\dfrac{dt}{dx} \right)}

\sf{I = \displaystyle\sin3x\cdot\dfrac{e^{2x}}{2} - \int \left(3\cos3x\cdot\dfrac{e^{2x}}{2}\right)dx}

\sf{\left(\because \dfrac{d(kx)}{dx}=k,when\:k\:is\:a\:constant. \right)}

\sf{I=\displaystyle\sin3x\cdot\dfrac{e^{2x}}{2} - \dfrac{3}{2}\int \cos3x\cdot e^{2x}\:dx}

\sf{\left(\because \displaystyle \int k\cdot f(x)\:dx=k\int f(x)\:dx,when\:k\:is\:a\:constant. \right)}

\sf{Take\:\displaystyle\int \cos3x\cdot e^{2x}\:dx=J}

\sf{I=\displaystyle \sin3x\cdot\dfrac{e^{2x}}{2} - \dfrac{3}{2}J}

Solving J,

\sf{J=\displaystyle \int \cos3x\cdot e^{2x}\:dx}

\sf{Taking\:u=\cos3x \:and\:v=e^{2x}\:as\:per\:ILATE.}

Applying Integration by parts,

\sf {J=\displaystyle\cos3x\int e^{2x}\:dx - \int \left(\dfrac{d(\cos 3x)}{dx}\int e^{2x}\:dx \right)dx}

\sf{J=\displaystyle \cos3x\cdot\dfrac{e^{2x}}{2} - \int \left(\dfrac{d(\cos 3x)}{dx}\cdot\dfrac{e^{2x}}{2}\right)dx}

\sf{J=\displaystyle \cos3x\cdot\dfrac{e^{2x}}{2} - \int \left(-\sin3x\cdot\dfrac{d(3x)}{dx}\cdot\dfrac{e^{2x}}{2}\right)dx}

\sf{\left(\because \dfrac{d(\cos t)}{dx}=-\sin t\cdot\dfrac{dt}{dx} \right)}

\sf{J=\displaystyle \cos3x\cdot\dfrac{e^{2x}}{2} +\int \left(3\sin3x\cdot\dfrac{e^{2x}}{2}\right)dx}

\sf{\left(\because \dfrac{d(kx)}{dx}=k,when\:k\:is\:a\:constant. \right)}

\sf{J=\displaystyle \cos3x\cdot\dfrac{e^{2x}}{2} + \dfrac{3}{2}\int \sin3x\cdot e^{2x}\:dx}

\sf{J= \cos3x\cdot\dfrac{e^{2x}}{2} + \dfrac{3}{2}I}

Substitute value of 'J' in 'I',

\sf{I=\displaystyle \sin3x\cdot\dfrac{e^{2x}}{2} - \dfrac{3}{2}J}

\sf{I=\displaystyle \sin3x\cdot\dfrac{e^{2x}}{2} - \dfrac{3}{2}\left( \cos3x\cdot\dfrac{e^{2x}}{2} + \dfrac{3}{2}I \right)}

\sf{I=\displaystyle \dfrac{\sin3x\cdot e^{2x}}{2} - \dfrac{3\cos3x\cdot e^{2x}}{4} - \dfrac{9}{4}I}

\sf{I+\dfrac{9}{4}I=\displaystyle\dfrac{2\sin3x\cdot e^{2x}}{4} - \dfrac{3\cos3x\cdot e^{2x}}{4}}

\sf{ \dfrac{13}{4}I= \dfrac{2\sin3x\cdot e^{2x}-3\cos3x\cdot e^{2x}}{4}}

\sf{ 13I= 2\sin3x\cdot e^{2x}-3\cos3x\cdot e^{2x}}

\sf{ I= \dfrac{2\sin3x\cdot e^{2x}-3\cos3x\cdot e^{2x}}{13}+C}

Answer :-

\underline{\boxed{\sf{\displaystyle \int e^{2x}\sin 3x\:dx= \dfrac{2\sin3x\cdot e^{2x}-3\cos3x\cdot e^{2x}}{13}+C}}}


Ataraxia: Awesome!! Thanks a lotttt!!!! (:
Anonymous: Supercalifragilisticexpialidocious!
amansharma264: nyccc
Answered by rohithkrhoypuc1
3

Answer:

I shared two attachment in that there is answer for your question. mam.

Hope it helps u mam

Attachments:
Similar questions